NIR and 1H qNMR methods coupled to chemometrics discriminate the chemotypes of the gastroprotective herb Egletes viscosa. (December 2020) - Carvalho, Kaline R.; Souza, Ana Sheila Q.; Alves Filho, Elenilson G.; Silva, Lorena Mara A.; Silva, Ebenézer O.; A. Pereira, Rita de Cássia; Zocolo, Guilherme J.; de Brito, Edy S.; Silveira, Edilberto R.; Canuto, Kirley M.
Graphical abstract: Highlights: Authenticity of the gastroprotective herb Egletes viscosa was determined. Chemotypes were discriminated using a portable NIR device on intact flower buds. Bioactive compounds were quantified by 1 H q NMR. Chemotype A contains more tanabalin and centipedic acid. Abstract: Egletes viscosa is a Brazilian medicinal herb consumed as flower bud tea due to its gastroprotective properties. This plant possesses two essential oil-based chemical varieties: trans -pinocarveyl acetate-rich chemotype A and cis -isopinocarveyl acetate- rich chemotype B. Therefore, we developed two simple, fast and reliable methods for discrimination of E. viscosa chemotypes using NIR and 1 H qNMR spectroscopies combined with the chemometrics tools (iPLS and PLS-DA). Both methods showed high sensitivity, precision and specificity in the cross-validation tests. The NIR method has the advantages of being non-destructive and analyzable by portable devices, enabling its application for field and industrial evaluations. Meanwhile, the 1 H qNMR method allows the quantification of the bioactive components ternatin, tanabalin, and centipedic acid. These aforementioned compounds were found higher in the chemotype A. Accordingly, our methods showed to be complimentary approaches for authenticity and/or quality control of E. viscosa -derived raw materials and herbal products.